Christianity and Sport Psychology: One Aspect of Cultural Competence - Trevor J. Egli; Leslee A Fisher (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2017)
There is currently a dearth of literature relating to how applied sport psychology practitioners might work with a Christian sportsperson (Czech et al., 2004, Egli et al., 2014). Therefore, the purpose of this article is to provide practical suggestions for sport psychology practitioners based on relevant research related to Christianity and sport psychology as well as personal and professional experience. We first explain the various sport psychology roles before providing a brief review of literature. Studies related to Christian athletes, Christian coaches, Christian prayer within sport, and sport psychology consultants’ experiences of spirituality are presented. Lastly, the authors include four practical steps for sport psychology practitioners who may encounter Christianity within their consulting relationships. These include: (a) education, (b) intake interview, (c) integrating Christianity into mental skills training, and (d) collaboration and/or referral.
Keywords: Christianity; sport psychology; Christian athlete; Christian coach; cultural competence